2005
DOI: 10.4028/www.scientific.net/msf.475-479.2251
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic Characteristics of Tb-Dy-Fe Polycrystals with <110> Axial Alignment

Abstract: The magnetostriction and dynamic characteristics of Tb0.27Dy0.73Fe2 polycrystals with <110> axial alignment were investigated by standard strain gauge, two coil induction and lock-in amplifier techniques. It is found that the magnetostriction of the sample quickly increases with increasing magnetic fields when H≤80 kA/m under a pressure of 5 or 10 MPa and a “jump” effect occurs during the magnetization process. The dynamic strain coefficient, d33, dynamic incremental permeability,μ33, and magneto-mechani… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
3
3

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 7 publications
0
10
0
Order By: Relevance
“…Wang et al [6] have investigated the magnetostrictive coefficient d 33 of Tb 0.27 Dy 0.73 Fe 2 single crystal and found that it can reach 8.6 nm/A along the /1 1 2S direction. Investigation of the magnetostrictive coefficient d 33 for the oriented Tb 0.27 Dy 0.73 Fe 2 polycrystal has found that the d 33 value is 6.5 nm/A [17]. It means that the magnetostrictive coefficient d 33 of 2-2 composite with the magnetic field heat treatment is less than that of Wang et al [6], but nearly same as the value of the oriented Tb 0.27 Dy 0.73 Fe 2 polycrystal [17].…”
Section: Resultsmentioning
confidence: 82%
See 1 more Smart Citation
“…Wang et al [6] have investigated the magnetostrictive coefficient d 33 of Tb 0.27 Dy 0.73 Fe 2 single crystal and found that it can reach 8.6 nm/A along the /1 1 2S direction. Investigation of the magnetostrictive coefficient d 33 for the oriented Tb 0.27 Dy 0.73 Fe 2 polycrystal has found that the d 33 value is 6.5 nm/A [17]. It means that the magnetostrictive coefficient d 33 of 2-2 composite with the magnetic field heat treatment is less than that of Wang et al [6], but nearly same as the value of the oriented Tb 0.27 Dy 0.73 Fe 2 polycrystal [17].…”
Section: Resultsmentioning
confidence: 82%
“…Investigation of the magnetostrictive coefficient d 33 for the oriented Tb 0.27 Dy 0.73 Fe 2 polycrystal has found that the d 33 value is 6.5 nm/A [17]. It means that the magnetostrictive coefficient d 33 of 2-2 composite with the magnetic field heat treatment is less than that of Wang et al [6], but nearly same as the value of the oriented Tb 0.27 Dy 0.73 Fe 2 polycrystal [17]. This result shows that the Terfenol-D 2-2 composite with the magnetic field heat treatment has an optimistic magnetostrictive property and can be used as a material for transducers.…”
Section: Resultsmentioning
confidence: 98%
“…Elastic and magnetoelastic properties of polycrystalline materials can be tuned by orienting the growth of all grains along a specific crystallographic direction [3][4][5]7]. In this section, we computationally explore how this effect influences the Young's modulus, magnetostriction and magnetocrystalline anisotropy energy for Terfenol-D. For this analysis we consider the same voronoi microstructure (seed 1) than in Section 3.2.1, but now the crystallographic direction < 011 > or < 111 > of all grains will be uniformly oriented to the z-axis with a dispersion angle δ.…”
Section: Influence Of Grain Orientationmentioning
confidence: 99%
“…The orientation of the grains in some specific crystallographic directions could be a convenient strategy to tune and enhance the elastic and magnetoelastic properties of polycrystalline Terfenol-D [3]. Wang et al investigated Terfenol-D polycrystals with < 110 > axial alignment finding excellent magnetostrictive properties under low magnetic fields [4]. Kown et al studied the effect of texture on the magnetostriction of grain-aligned composite Terfenol-D and confirmed that the effective magnetostriction depends on the preferred growth direction [5,6].…”
Section: Introductionmentioning
confidence: 99%
“…The elastic modulus of Tb 0.3 Dy 0.7 Fe 2 alloy is dependent on its stress state [1] and the magnetic field applied to it [2]. The magnetic field dependence of magnetostriction for Tb 0.3 Dy 0.7 Fe 2 alloy under different mechanical loads has been investigated [3][4][5]. Reference [6] reported stress-strain curve of Tb 0.3 Dy 0.7 Fe 1.92 alloy, oriented along [112] direction, under different magnetic fields and found that it is nearly linear without magnetic fields.…”
Section: Introductionmentioning
confidence: 99%